Neuronal Ceroid Lipofuscinosis: The Multifaceted Approach to the Clinical Issues, an Overview - Simonati, Alessandro; Williams, Ruth E. (Frontiers in Neurology, 2022)
The Neuronal Ceroid Lipofuscinoses (NCL) are the most frequent genetically determined, neurodegenerative disorders of childhood (Batten disease). They form a heterogeneous group of lysosomal storage diseases mainly affecting brain and retina. Amaurosis, cognitive decline, motor impairment, untreatable epilepsy are considered as the most relevant clinical hallmarks shared between the forms. NCL definition relies on pathological criteria: the presence of autofluorescent lipofuscin and the characteristic endolysosomal storage. Clinically they are divided into four groups according to the age of onset (infantile, 6-18 months of age, late infantile 2-4 years, juvenile after 5 years, and the ultra-rare connatal form). They are progressive disorders with fatal outcome. There is no curative treatment. NCL are rare disorders with world-wide distribution. Epidemiological data indicate incidence of 1-3/100000 and a prevalence of about 2-4/1.000.000. Childhood NCLs are inherited as autosomal recessive diseases. Thirteen NCL genes have been identified so far and an equivalent number of NCL forms are currently considered in NCL nosography. The availability of genetic diagnosis has allowed more accurate predictions for the clinical course and outcome of those children who present a "classical" phenotype according to the underlying genetic diagnosis; clinical variants are also known due to mutations in several NCL genes. Five NCL genes code for lysosomal proteins; the remaining eight genes encode for trans-membrane proteins of different cellular domains, a component of a potassium channel and proteins of the cytosolic domain. The precise function has been partially elucidated for a number of proteins only. Given such heterogeneity the pathological mechanisms leading to storage formation and cell death remain obscure. Impaired autophagy is the only identified mechanism, Dysfunction of cellular organelles, the mitochondria and the endoplasmic reticulum, occur in some NCL forms. NCL are progressive disorders with fatal outcome. Palliative care and symptomatic treatments have been the only therapeutic interventions so far. Innovative therapies are becoming available and combined treatments are predicted in clinical trials. At present there is only one registered drug (the missing enzyme delivered into intracerebral ventricules to CLN2 patients). Within a decade (or even less) the results of the combined efforts may lead to successful treatments for NCLs.